Hematologic dysfunction in cancer: Mechanisms, effects on antitumor immunity, and roles in disease progression - Plackoska, Viktoria; Shaban, Dania; Nijnik, Anastasia (Frontiers in Immunology, 2022)
With the major advances in cancer immunology and immunotherapy, it is critical to consider that most immune cells are short-lived and need to be continuously replenished from hematopoietic stem and progenitor cells. Hematologic abnormalities are prevalent in cancer patients, and many ground-breaking studies over the past decade provide insights into their underlying cellular and molecular mechanisms. Such studies demonstrate that the dysfunction of hematopoiesis is more than a side-effect of cancer pathology, but an important systemic feature of cancer disease. Here we review these many advances, covering the cancer-associated phenotypes of hematopoietic stem and progenitor cells, the dysfunction of myelopoiesis and erythropoiesis, the importance of extramedullary hematopoiesis in cancer disease, and the developmental origins of tumor associated macrophages. We address the roles of many secreted mediators, signaling pathways, and transcriptional and epigenetic mechanisms that mediate such hematopoietic dysfunction. Furthermore, we discuss the important contribution of the hematopoietic dysfunction to cancer immunosuppression, the possible avenues for therapeutic intervention, and highlight the unanswered questions and directions for future work. Overall, hematopoietic dysfunction is established as an active component of the cancer disease mechanisms and an important target for therapeutic intervention.